2013
DOI: 10.1371/journal.pone.0079530
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactoglobulin's Conformational Requirements for Ligand Binding at the Calyx and the Dimer Interphase: a Flexible Docking Study

Abstract: β-lactoglobulin (BLG) is an abundant milk protein relevant for industry and biotechnology, due significantly to its ability to bind a wide range of polar and apolar ligands. While hydrophobic ligand sites are known, sites for hydrophilic ligands such as the prevalent milk sugar, lactose, remain undetermined. Through the use of molecular docking we first, analyzed the known fatty acid binding sites in order to dissect their atomistic determinants and second, predicted the interaction sites for lactose with mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…BLG with its molecular mass of 18.3 kDa contains 162 amino acid residues and its main binding site is postulated to be at its calyx entrance. An accessibility of the calyx for a guest molecule is known 44 to be a pH dependent: at pH lower than 6.5, the EF loop, a motif of this macromolecule containing the residues from I 84 to N 90, remains closed and it opens up at pH >7. 44 The results of the performed molecular docking suggest that each of the clathrochelate molecules is able to t the entrance of the BLG cavity, in which it forms the bonds with amino acid residues of the protein (mainly through the nonpolar dispersion interactions).…”
Section: Molecular Docking Of a Clathrochelate Binding To Blgmentioning
confidence: 99%
See 1 more Smart Citation
“…BLG with its molecular mass of 18.3 kDa contains 162 amino acid residues and its main binding site is postulated to be at its calyx entrance. An accessibility of the calyx for a guest molecule is known 44 to be a pH dependent: at pH lower than 6.5, the EF loop, a motif of this macromolecule containing the residues from I 84 to N 90, remains closed and it opens up at pH >7. 44 The results of the performed molecular docking suggest that each of the clathrochelate molecules is able to t the entrance of the BLG cavity, in which it forms the bonds with amino acid residues of the protein (mainly through the nonpolar dispersion interactions).…”
Section: Molecular Docking Of a Clathrochelate Binding To Blgmentioning
confidence: 99%
“…An accessibility of the calyx for a guest molecule is known 44 to be a pH dependent: at pH lower than 6.5, the EF loop, a motif of this macromolecule containing the residues from I 84 to N 90, remains closed and it opens up at pH >7. 44 The results of the performed molecular docking suggest that each of the clathrochelate molecules is able to t the entrance of the BLG cavity, in which it forms the bonds with amino acid residues of the protein (mainly through the nonpolar dispersion interactions). To check an ability of the polar interactions between the amino acid residues and the clathrochelate molecule, we also performed its docking procedure with the residues Leu 46, Leu 54, Ile 56, Ile 71, Ile 84, Phe 105, Met 107, Lys 60, and Lys 69 set as exible.…”
Section: Molecular Docking Of a Clathrochelate Binding To Blgmentioning
confidence: 99%
“…It belongs to the lipocalin family of small extracellular proteins that carry hydrophobic ligands [11]. BLG is relevant to the food industry due to its binding spectrum and abundance in cow's milk; thus, it has been extensively characterized, biochemically and structurally, through X-ray diffraction (XRD), NMR and computational approaches [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Each BLG monomer consists of 162 residues (18.3 kDa), folded into eight-stranded antiparallel β-sheets that form a hydrophobic binding pocket called the calyx (shown in Figure 1 and Figure S1), flanked by an α-helix [16]. BLG binds to a variety of nutrients like fatty acids, peptides, sugars and some vitamins ( Figure S2) in at least two different binding sites, the most prominent of which is the calyx [15,17,18] (the second site is formed in the interphase between two BLGs when they dimerize [15], and will not be explored here). The affinity for the known hydrophobic ligands in the calyx is in the micromolar range [19].…”
Section: Introductionmentioning
confidence: 99%
“…9,10,14,15 Crystal and NMR structures revealed that BLG has a hydrophobic core of eight antiparallel β-strands (A-H) forming a β-barrel (or calyx) showing a pH dependent accessibility mediated via a conformational change of the flexible loop connecting strands E and F (EF-loop-residues 85-90). 10,16 At pH >7.0 this loop adopts an open conformation as seen in different crystal structures (1BEB, 1BSY, 1B0O, 2Q2M, 2BLG), 1,14,1719 whereas at pH <7.0 a closed form is found in crystal and NMR structures (1CJ5, 2AKQ and 3BLG). 19,20,21 In solution BLG is present in different oligomerization states depending on pH, ionic strength and temperature.…”
Section: Introductionmentioning
confidence: 99%